The Relationship between Business Environment and Management Strategy - Ngo Ngoc Minh, (International Journal of Psychosocial Rehabilitation, 2020)
The paper used the structured formula to examine the relationship between business environment and management strategy over the data of 177 questionnaires collected from respondents in Thanhhoa province-Vietnam. The empirical results indicated some points as: first, the business environment including technological strength, competitive strength, government support policy, and financial support had a significant impact on management strategy; second, management strategies had a significant impact on business performance. This means that in order for an entity to settle in the market, it is essential to establish a discriminatory management strategy in various business environments.